2015
DOI: 10.1080/10408398.2014.889653
|View full text |Cite
|
Sign up to set email alerts
|

Camellia sinensis in asymptomatic hyperuricemia: A meta-analysis of tea or tea extract effects on uric acid levels

Abstract: Flavanols of Camellia sinensis exhibit uric acid (UA) lowering effect, through the modulation of both xanthine oxidase and urate excretion. In order to investigate the potential benefit of Camellia Sinenis products in asymptomatic hyperuricemia, a meta-analysis of long-term Randomized Controlled Trials (RCT) with tea or tea extract has been conducted. From 20 human intervention studies selected only 5 RCT (13 interventions) were suitable for meta-analysis (n = 472). The current "normal" range set for hyperuric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 67 publications
1
24
0
1
Order By: Relevance
“…As shown in Table , theaflavins and catechins inhibit xanthine oxidase (XO) activity and UA production in vitro : theaflavin 3,3′‐O‐digallate (10 −6 M) and EGCG (10 −7 M) act as competitive inhibitors (Aucamp et al , ; Lin et al , ). Despite the effect of theaflavins and catechins as XO inhibitors, in a meta‐analysis reviewing human intervention studies that measured UA after tea products, no significant differences were observed between BT, GT and GTE (Peluso et al , ). However, it must be taken into account that many studies had UA as secondary outpoint and did not consider the fact that the normal range of UA differs in males and females.…”
Section: Enzymatic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table , theaflavins and catechins inhibit xanthine oxidase (XO) activity and UA production in vitro : theaflavin 3,3′‐O‐digallate (10 −6 M) and EGCG (10 −7 M) act as competitive inhibitors (Aucamp et al , ; Lin et al , ). Despite the effect of theaflavins and catechins as XO inhibitors, in a meta‐analysis reviewing human intervention studies that measured UA after tea products, no significant differences were observed between BT, GT and GTE (Peluso et al , ). However, it must be taken into account that many studies had UA as secondary outpoint and did not consider the fact that the normal range of UA differs in males and females.…”
Section: Enzymatic Inhibitionmentioning
confidence: 99%
“…Apart from their antioxidant activity, tea flavanols could also have other activities of pharmacological interest, such as the ability to lower glucose (Liu et al , ; Zheng et al , ), lipid (Zheng et al , ; Hartley et al , ; Onakpoya et al ., ) and uric acid (UA) (Peluso et al , ) concentrations. These activities could be mediated by their effects on various enzymes and transporters (Peluso et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The data extracted from each study included the first-author's name, year of publication, country of the study performed, ethnicity, subject characteristics, type of BT, comorbidities, method of evaluation of TAC and other markers of plasma redox status. For each study with more than one beta-thalassemic group, we divided the control group evenly according to the number of disease groups [14]. When the data were presented as standard error of means (SEM), standard deviation (SD) was obtained by multiplying SEM by the square root of the sample size [14].…”
Section: Data Extractionmentioning
confidence: 99%
“…For each study with more than one beta-thalassemic group, we divided the control group evenly according to the number of disease groups [14]. When the data were presented as standard error of means (SEM), standard deviation (SD) was obtained by multiplying SEM by the square root of the sample size [14]. Data extraction was performed independently by two reviewers (H.M. and G.D.) to ensure uniformity.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation